1960
DOI: 10.3382/ps.0390385
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and Anatomic Adaptations in Chickens “Trained” to Eat Their Daily Food in Two Hours

Abstract: EXPERIMENTALMale chicks weighing 600 to 800 grams were trained to eat their daily food intake in two hours. They were trained for periods 385 at NERL on June 9, 2015

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

1970
1970
2007
2007

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…Meal-feeding was also associated with increased length and reduced weight per length-unit (g/cm) of the small intestine. A thinner intestine conforms to the suggestion of Lepkovsky et al (1960) who proposed that meal-feeding increases the flexibility of the intestinal wall, thereby enabling excessive amounts of chyme to be accommodated and increasing the rate of absorption.…”
Section: Discussionsupporting
confidence: 65%
“…Meal-feeding was also associated with increased length and reduced weight per length-unit (g/cm) of the small intestine. A thinner intestine conforms to the suggestion of Lepkovsky et al (1960) who proposed that meal-feeding increases the flexibility of the intestinal wall, thereby enabling excessive amounts of chyme to be accommodated and increasing the rate of absorption.…”
Section: Discussionsupporting
confidence: 65%
“…Lee et al (1971) have pointed out that imposing feed restriction on growing pullets by limiting the time of access to food is an unsatisfactory restriction technique since the birds will quickly learn to eat normal quantities of food in a short time period. The results of Lepkovsky et al (1960) indicated that young cockerels could be trained to eat their daily requirements in 2 hr. However, 1 4-6 week training period was necessary.…”
Section: Resultsmentioning
confidence: 98%
“…According to Williams et al (1997) and Ferket (2000), the coarse nature of whole wheat probably enhances the development of the gizzard, allowing improved grinding, gut motility and nutrient utilisation. Moreover, it has been shown that chickens trained to eat rapidly had larger amounts of feed in the crops than untrained chicks, which probably reflects the higher capacity of the crop in trained chickens (Lepkovsky et al, 1960). In the present experiment, the content of supplementary feed was significantly higher in crops from wheat-fed hens, but because of different retention times in the crops for wheat and layer feed (Heuser, 1945) the contents of these feed items do not reflect the differences in feed intake as indicated by Table 4 and Figure 1.…”
Section: Discussionmentioning
confidence: 99%